Kadal dan Ular (Reptil: Squamata) di Taman Nasional Gunung Palung Sebagai Sumber belajar biologi - Ramadhan Ardiyanto; Anandita Eka Setiadi; Mahwar Qurbaniah (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze the Squamata order in Gunung Palung National Park as a learning resource. The study was condicted through 2 stages. First to identify the diversity of squamata in SRCP TNGP with observation Visual Encounter Survey. Second to analyze the potiend of squamata diversity as biology learning resource using questionnaire to analyze the potential data as biology learning resource. The research findings revealed 15 individuals from 10 species and 6 families of the Squamata order. Based on the results and feedback from 8 respondents, squamata order is considered suitable as a learning resource. The requirements for a learning resource include clear potential, clear learning objectives, alignment with learning goals, clarity of information provided, clear exploration guidelines, and clear expected outcomes. The results of the lizard and snake inventory study in TNGP, as a biology learning resource, align with the attainment of basic competencies in the field of biology, encompassing various levels of biodiversity, ecology, and environmental change, specifically in the subtopic of environmental conservation, suitable for class X high school.